Getting order in mesostructured thin films, from pore organization to crystalline walls, the case of 3-glycidoxypropyltrimethoxysilane1. Issue 16 (28th April 2015) - Carboni, Davide; Pinna, Alessandra; Amenitsch, Heinz; Casula, Maria F.; Loche, Danilo; Malfatti, Luca; Innocenzi, Plinio
<x xml:space="preserve">Abstract</x> A new type of hybrid organic–inorganic film showing long-range ordered mesostructure and crystalline pore walls has been successfully prepared.